Anatomical description of scapulocoracoid and gill arches of Benthobatis kreffti - Junior, Ítalo Rafael Bini [UNESP]; dos Santos, Camila Mayumi Hirata [UNESP]; Gadig, Otto Bismarck Fazzano [UNESP] (My University, 2015)
This study describes the scapulocoracoid and the ventral gill arches of a rare benthic elasmobranch, Benthobatis kreffti, based on specimens collected at depth of 500 m offthe coast of São Paulo state, southern Brazil. The scapulocoracoid has an anterior fontanelle that is placed laterally. Condyles are similar in size, unequally spaced, and they are not aligned horizontally. The mesocondyle is located below the other condyles. The posterior fenestrae are allocated within the cartilage of the scapulocoracoid, while the anterior fenestrae cross its lateral-posterior segment. The suprascapula is arched posteriorly, and it is not connected or fused to the synarcual or the vertebral column. Three unfused hypobranchial elements were found in the ventral gill arches. The ceratobranchials are rod-like shaped, with fenestrae from first to fourth ceratobranchials. The fifth is morphologically distinct and connected to the scapulocoracoid. There is a pair of elements above the basibranchial copula, of unknown origin, also reported for other congeneric species, Benthobatis marcida. Such character could represent an autapomorphy of the genus.
Keywords: Anatomy; Chondrichthyes; Electric ray; Skeleton; Torpediniformes